2012
DOI: 10.1016/j.yexcr.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of SWI/SNF chromatin remodeling factor subunits modulates cisplatin cytotoxicity

Abstract: Chromatin remodeling complex SWI/SNF plays important roles in many cellular processes including transcription, proliferation, differentiation and DNA repair. In this report, we investigated the role of SWI/SNF catalytic subunits Brg1 and Brm in the cellular response to cisplatin in lung cancer and head/neck cancer cells. Stable knockdown of Brg1 and Brm enhanced cellular sensitivity to cisplatin. Repair kinetics of cisplatin DNA adducts revealed that downregulation of Brg1 and Brm impeded the repair of both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 46 publications
3
44
2
Order By: Relevance
“…It should be noted that some of these studies have reported functional differences, which is likely due to the comparison of cell lines derived from different tissue/tumor types that each have a unique genetic background. For example, BRG1 and BRM depletion had a much stronger effect on the survival of lung cancer cells [62] than what we observed for cervical cancer cells in this study.…”
Section: Discussioncontrasting
confidence: 51%
“…It should be noted that some of these studies have reported functional differences, which is likely due to the comparison of cell lines derived from different tissue/tumor types that each have a unique genetic background. For example, BRG1 and BRM depletion had a much stronger effect on the survival of lung cancer cells [62] than what we observed for cervical cancer cells in this study.…”
Section: Discussioncontrasting
confidence: 51%
“…In addition, SWI/SNF in general has been shown to play roles in cellular differentiation and organ development 4549 . Interestingly, the SWI/SNF complex may also increase sensitivity to cisplatin 50 but increase resistance to EGFR inhibitors. Indeed, there is no shortage of feasible mechanisms by which BRM loss could impact cancer development and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the genes constituting this panel serve as biomarkers for efficacy, prognosis, diagnosis, disease progression (targeting inflammation, oxidative stress and vesiculation gene networks) and response to therapy [43,44,45,46,47,48,49,50,51,52,53,54,55,56,57]. Vitamin D mediated genetic networks such as those identified in our study, for example inflammation, oxidative stress and membrane vesicle biogenesis pathways in 143B cells, shed insight into the mechanism(s) underlying antineoplastic effects of vitamin D in human OS.…”
Section: Discussionmentioning
confidence: 99%